IDENTIFICATION OF WILD PLANTS AS A REFUGIA PREDATOR AND ORANGE PLANT PARASITOID (Citrus grandis) IN JERUK DESA KERONGKONG DISTRICT LOMBOK TIMUR - Muliawan, Wawan (UNIVERSITAS HAMZANWADI, 2020)
Control of Plant Pest Organisms by using synthetic pesticides has a negative impact on the garden. Some of these impacts include environmental pollution, the emergence of